Effect of Forest Management on Carbon Stock of Tropical Moist Afromontane Forest - Damena Edae Daba; Bikila Workineh Dullo; Teshome Soromessa (International Journal of Forestry Research)
Moist tropical forests have a significant role in provisioning and regulating ecosystem services. However, these forests are under threat of deforestation and forest degradation. In Ethiopia, the moist evergreen Afromontane forests have the potential for carbon storage and support a high diversity of plant species. However, it is under severe threat of deforestation and degradation.This investigation was conducted to obtain adequate information on the carbon stock potential of the moist Afromontane forest of southwestern Ethiopia. A comparison of carbon stock was conducted between disturbed and undisturbed forests. A systematic sampling design was applied for recording woody species and soil data. A total of 100 main plots of 400 m2 were laid to record trees and shrubs with a diameter at breast height (DBH) ≥ 5 cm. The soil data were collected from 1 m2 subplots established at the four corners and the center of each main plot. The DBH and height were measured to calculate the aboveground carbon of trees and shrubs with DBH ≥ 5 cm. A total of 68 tree and shrub species belonging to 59 genera and 33 families were recorded. The mean carbon stock density was 203.80 ± 12.38 t·ha–1 (aboveground carbon stock) and 40.76 ± 2.47 t·ha–1 (belowground carbon stock). The highest proportion of aboveground carbon (t·ha–1) (42.34%) was contributed by a few tree individuals with DBH > 70 cm. The soil organic carbon stock (SOCS) (t·ha–1) for the depth of 0–30 cm is ranging from 58.97 to 198.33 across plots; the mean is 117.16 ± 3.15. The carbon stored in the moist Afromontane forest indicates its huge potential for climate change mitigation. Therefore, for the enhancement of forest biodiversity and carbon sequestration effective conservation measure and sound management approach is essential.